2021
DOI: 10.1162/asep_a_00797
|View full text |Cite
|
Sign up to set email alerts
|

How Did Japan Cope with COVID-19? Big Data and Purchasing Behavior*

Abstract: Japan has been recognized as having successfully controlled the spread of the coronavirus pandemic. This study aims to gather insights to combat the spread of infection in our daily lives by observing our purchasing behavior. We use Point of Sales (POS) data from supermarkets, convenience stores, home centers, drug stores, and electronics retail stores for a nationwide analysis. Our analysis revealed the following. First, the Japanese people actively prevented the spread of infection by voluntarily wearing mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…However, examples of misinformation spread through sources other than social media have also been reported, such as the fake news about the shortage of toilet paper due to the COVID-19 pandemic since most toilet papers are made in China. This news spread in Japan in February and March 2020 [ 10 ]. When asked where they received this information, nearly 60% of the participants stated that television (TV) was the most common source [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, examples of misinformation spread through sources other than social media have also been reported, such as the fake news about the shortage of toilet paper due to the COVID-19 pandemic since most toilet papers are made in China. This news spread in Japan in February and March 2020 [ 10 ]. When asked where they received this information, nearly 60% of the participants stated that television (TV) was the most common source [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Populations pre-experienced in viral epidemics adopted preventive measures with good risks and bene ts, which is defended, such as social distancing, washing hands, wearing masks, and gargling/rinsing with antiseptic solutions. [18][19][20][21] Since saliva was an important source of virus transmission during the pandemic, protective measures, such as the use of antiseptic gargles were adopted and recommended by several countries and organizations against SARS-CoV-2. 5,10,[21][22][23] Some studies have shown that the use of a mouthwash containing APD can reduce the viral load of SARS-CoV-2, acting as a therapeutic aid in reducing the severity and risk of COVID-19 transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Some companies provide their business-transaction data to researchers. Especially after the onset of COVID-19, economists collaborated with banks, mobile carriers, and financial technology companies to analyze behaviors during the pandemic (Kaneda, Kubota, and Tanaka 2021; Konishi et al 2021; Kubota, Onishi, and Toyama 2021); however, to our knowledge, few political scientists have used these data. An annotated list of online data resources for Japanese politics work is available in the online appendix, and we encourage researchers to investigate whether analogs exist in their areas or countries of interest.…”
Section: Recommendations For Researchersmentioning
confidence: 99%